The consolidation of social assistance in Brazil and its challenges, 1988-2008 - Luciana Jaccoud; Patricia Dario El-Moor Hadjab; Juliana Rochet Chaibub (International Policy Centre for Inclusive Growth (IPC-IG), 2010)
[Introduction ...] The paper is divided into six sections, including this introduction. Section 2 briefly describes the 1988 constitution and its main contributions to the policies under discussion. Section 3 examines cash transfer programmes under social assistance: the Continuous Cash Benefit (Benefício de Prestaç\~ao Continuada, BPC) and the Bolsa Família programme (Programa Bolsa Família, PBF). Section 4 looks at the effort to reorganise the supply of social assistance services, with an emphasis on the establishment and improvement of the Unified Social Assistance System (Sistema Único de Assistência Social, SUAS). Section 5 addresses the policy's main challenges today. The final section offers concluding remarks.
Keywords: 330; Sozialhilfe; Brasilien